A retrospective description of blood and urine alterations in 386 male cats with urethral obstruction in Botucatu, Sao Paulo, Brazil - Reiner Silveira de Moraes; Diego Ribeiro; Alessandra Melchert; Henry David Mogollón García; Doughlas Regalin; Raphael Lucio Andreatti Filho; Rogerio Giuffrida; Regina Kiomi Takahira; Adriano Sakai Okamoto; Priscylla Tatiana Chalfun Guimaraes-Okamoto (Open Veterinary Journal)
Background: Urinary retention in obstructed male cats leads to changes in blood and urine compounds, which, combined with the time of obstruction, are linked to worsening of the animal's clinical status.